Pembelajaran Maharah Al-Istima - Hamidah Hamidah; Marsiah Marsiah (Universitas Islam Negeri Palangka Raya, 2020)
In learning Maharah al-Istima, a lecturer at a college in Palangka Raya uses films from Youtube. Learning to listen to a foreign language cannot separated from problems, but students try to find solutions. This qualitative descriptive study aims to explore the use of films from Youtube in Maharah al-Istima's learning, listening problems and their solutions. The data were collected through observation, interview and documentation techniques, and the data were analyzed through the stages of data collection, data reduction, data presentation and conclusion drawing. The results showed that the lecturer used movies from Youtube offline and online by collecting, selecting, verifying credibility and evaluating the quality of the film. This activity trains students to listen to Arabic and increase their knowledge so that the results of listening of the students are good. The problems faced by students while learning to listen are the fast Arabic pronunciation, the lack of clarity in conversations and the difficulty in vocabulary. Students solve the first problem by playing back, focusing on listening or using dictionaries and other learning strategies. For the second problem, the students overcome them by focusing and understanding the context of the sentences, using a dictionary or other learning strategies. For the third problem, the solution is to train hearing, using a dictionary and reading frequently. The implication of this study is that multimedia communication can help improve the student's listening ability in both offline and online learning.